Increasing the Link‐distance of Free‐space Quantum Coherent Communication with Large Area Detectors - Rupesh Kumar; Igor Konieczniak; Gerald Bonner; Tim Spiller (IET Quantum Communication, 2021)
Abstract A large area photo‐diode based homodyne detector for free‐space quantum coherent communication is reported. The detector's performance is studied in terms of the detection bandwidth and electronic noise for shot‐noise limited quantum signal detection. Using large area photo‐diodes increases the signal collection efficiency from turbulent atmospheric channels, in comparison with thetypical fibre‐based free‐space homodyne detectors. Under identical atmospheric turbulence and receiver aperture conditions, over a 700‐km free‐space link at 90° elevation angle, our homodyne detector based on a diameter of 1mm photo‐diode experiences 0dB loss due to turbulence, while a 10‐um fibre‐based detector experiences 13.5dB of signal loss.